Herpes simplex virus type 1-specific cytotoxic T lymphocytes recognize immediate-early protein ICP27. - Banks, T A (1991)
The identity of herpes simplex virus type 1 (HSV-1) antigens that serve as targets for cytotoxic T lymphocytes (CTL) and their ability to induce protective immunity remain uncertain. In this article, we report the identification of the immediate-early protein ICP27 as a CTL antigen in H-2d mice but not in H-2k or H-2b mice. Calculation of the frequencies of H-2d-restricted virus-specific CTL demonstrated that approximately one-fourth of the total HSV-1-specific response was directed against ICP27. To define the location of this CTL epitope, four truncated derivatives of the ICP27 gene which place the epitope in a 217-amino-acid region (amino acids 189 to 406) near the central portion of the protein were constructed. Mice immunized with ICP27 were able both to induce HSV-1-specific CTL and to survive a lethal intraperitoneal challenge with virulent HSV-1. However, neither appreciable antibody nor delayed-type hypersensitivity responses were induced in immunized mice, and they were also unable to clear a local epithelial virus challenge. It appears that ICP27, although capable of inducing several aspects of the immune response, is by itself unable to provide complete immunity.